Creating an environment that encourages both extensive and intense threaded dialogue The growth of discussion threads and the size of the class - Susan Hilliard; Madeline Ledger; Natasha Power (International Journal of Advanced Science and Computer Applications, 2022)
The purpose of this research is to investigate the beginning and development of asynchronous discussion threads in various class sizes over the course of 25 graduate-level courses and 22 interviews. The paper also aims to create some recommendations for promoting threaded discourse during the initiation, advancement, summary, and evaluation phases of a discussion thread from pedagogical, technological, and theoretical viewpoints. The statistical analysis revealed that class size did influence the number of threads and the length of threads created by students and instructors, which showed the importance of certain themes in the conversation. The majority of participants said that it was difficult to follow threaded conversations in order to establish meaningful cooperation in huge classrooms. Instructors and graduate students each expressed a preference as to whether they should begin or follow a conversation. Some pedagogical tactics were used by the instructors to facilitate the commencement and growth of discussion threads. This research may have consequences for both practitioners and academics in terms of developing new software features and designing efficient educational tactics in order to produce more successful comprehensive and intense knowledge-building discourse in the classroom.